Due interventi di Paolo VI sull’esistenza ed azione del demonio - Barrajón LC, Pedro (Alpha Omega, 2013)
At a time in the Church’s history when many Catholics were awaiting from the Second Vatican Council many fruitful benefits, they found instead only confusion and incertitude. Pope Paul VI sees the devil as having a certain causal role in this situation and in two major interventions recalls the main point of the Catholic doctrine on devil. The first was his homily of the feast of the Apostles Peter and Paul (29th June 1972) and the second a Catechesis on the Our Father (12th November 1972). Both interventions received much publicity because at the time some Theologians denied the existence of devil as a mythical interpretation of evil. Paul VI was clear in these interventions but at the same time sensitive and prudent. The author examines these two interventions of Pope Paul VI and situates them in their particular historical context. He also analyzes the theological, spiritual and ecclesiological consequences of the Pope’s interventions.